The war of the worlds - Miller, Harry (Harry Glickman) (Classics illustrated (Newbury (England)), 2018)
Presents a graphic adaptation of H.G. Wells' classic story of an attack by Martian invaders on the planet Earth that forces a man named George to find a way to survive a planet-wide war.